Revolt! Act III - Benjamin Davidson (EJP import test, 2021)
[caption id="attachment_2357" align="alignleft" width="1024"] "Inferno" by Stephen Mosblech[/caption] Summary: How to convey the lexical and temporal paradoxes of psychoanalytic practice—their proper potencies and potentialities, their urgent stakes—in plague times? One tack: faced with scourges at once epidemiological, political and discursive, fabricate an eccentric, looping or forking itinerary out of italicized citations from Malaparte, Gadda, Serres, Lacan, Benjamin, Pasolini, Agamben and Braunstein. Deploy smells, case material, tableaux, literary and reportorial fictions; employ Baroque and allegorical figural modes and the antitheses embedded in (equivocal) words themselves in an effort to articulate and transmit, amid the swirl of diverse contemporary pestilences, the uniquely psychoanalytic ethics put forward by Lacan: he upholding of a desire allowing the signification of a limitless love to emerge from beyond the limits of the law, where alone it may live.
Keywords: baroque; Malaparte; plague; Serres; Smell